Pattern of Kidney Injury Molecule-1 in Different Stages of Chronic Kidney Disease (Bangladesh Renal Journal, 2026)
In clinical practice, the evaluation of renal function is performed by measuring serum creatinine to calculate glomerular filtration rate (eGFR) and urinary albumin (uACR). Both indices mainly reflect glomerular damage in the kidney. But tubular injury is also important in the pathogenesis of renal disease and appears to precede glomerular injury. Kidney injury molecule-1 (KIM-1), a transmembrane glycoprotein, is considered as a potential biomarker of renal tubular injury. The aim of the study was to find out the correlation of urinary KIM-1 levels with the stages of chronic kidney disease (CKD) and its association with the progression of the disease. In this cross-sectional study, total 100 CKD patients from all stages and 28 healthy controls were included. Urinary KIM-1 was measured through enzyme-linked immunosorbent assay. Urinary KIM-1 was indexed to urine creatinine (KIM-1/Cr ratio) by dividing urinary concentration of KIM-1 by urinary creatinine concentration to account for the concentration of urine. Among the case group 13% (n=13) had stage 1and stage 2, 15% (n=15) had stage 3a, 22% (n=22) had stage 3b, 22% (n=22) had stage 4 and 28% had stage 5 CKD. The mean age of the CKD patients were 53 years. Among them 64% were male. The mean urinary KIM 1/Cr level was significantly higher in case group than in control group (940.96±192.98 vs. 497.20± 39.60 pg/ mg; P< 0.001) with trends of higher values with the advancement of stages of CKD. Urinary KIM-1 levels correlated with traditional markers of renal damage and had the potential to predict the progression of CKD which could be explored further in longitudinal studies.Bang. Renal J. 2026; 8(1): 24-29